Analysis of modern trends in labour market transformation in Ukraine - Mazniev, Ievgen; Bielousov, Yaroslav; Luchechko, YuriI; Rozbytskyi, Mykhailo; Kolosok, Andrii; Shepelenko, Svitlana; Dziamulych, Mykola (My University, 2024)
The article examines the main aspects of transforming the labor market in Ukraine in the context of the destructive impact of the war and the associated economic instability. The primary factors affecting the labor market, such as migration processes, changes in the structure of employment, digitization of the economy, and the introduction of the latest technologies, are considered. The consequences of military operations on the transformation of the labor market are analyzed. Current trends in the demand for new professions, demographic changes, and the impact of state regulatory policy on employment support are explored. The prospects for developing the labor market in the context of Ukraine's European integration and the potential for increasing the competitiveness of Ukrainian workers in the European labor market are determined. The necessity of enhancing the adaptability of the workforce to modern challenges and optimizing state employment programs to ensure sustainable economic development of the country in the future has been demonstrated.
Keywords: labor market; migration; workforce; rural population; market transformation; management; employment structure; state employment support; reintegration into the economy; globalization; inclusive labor market; reintegration into civil society; veterans